Prone Position Reduces Spontaneous Inspiratory Effort in Patients with Acute Respiratory Distress Syndrome: A Bicenter Study - Yoshida, T (2021)
This study was approved by the Ethics committee for Clinical Studies, Osaka University Hospital, Suita, Japan (No. 18051), and Hospital Rebagliati, Lima, Perú (No. 2798), and it was performed before the coronavirus disease (COVID-19) pandemic. Patients were eligible if their age was 18 years or older, if they met criteria for moderate-to-severe ARDS as per the Berlin definition (5), and if prone position was planned based on the attending physicians’ decisions.